Time, space, and metaphysics - Rundle, Bede. (Oxford : Oxford University Press, 2009)
'Time, Space, and Metaphysics' engages with major philosophical questions concerning time and space, a framework for the investigation being provided by the debate between the absolutists and the relationists.
Description based on print version record.
Includes bibliographical references.
Keywords: Space and time